Detection of Adulteration of Soy Sauce by Brine Using Near Infrared Spectroscopy - T. Natcha; S. Panmanas (My University, 2014)
Abstract Near infrared spectroscopy was applied for determination of adulteration of soy sauce with brine. Thirty samples with 5 brands were bought from department stores and flea markets. Five samples were fabricated of 20% w/w brine, mono sodium glutamate and black soy sauce. Thirty five samples of 7 levels of 20% brine adulterated (10, 20, 30, 40, 50, 60 and 70%) were prepared. Each sample was scanned with FT-NIR spectrometer. A PLS regression model for percentage of brine adulterated provided R2, RMSEP, RPD and bias 92.73%, 6.42%, 4.61% and 3.81, respectively.
Keywords: Brine; Spectroscopy and Chemometric Analyses